Credit Risk as Moderating Effect of Minimum Capital Adequacy Requirement, Credit Distribution and Efficiency Operational to Profitability - Ni Kadek, Diana Yasmini (Universitas Pendidikan Ganesha, 2022)
Abstract This study aims to determine: (1) to determine the effect of minimum capital adequacy on profitability, (2) to determine the effect of lending on profitability, (3) to determine the effect of operational efficiency on profitability, (4) to determine the effect of capital adequacy obligations minimum on profitability moderated by credit risk, (5) to determine the effect of lending on profitability moderated by credit risk, and (6) to determine the effect of operational efficiency on profitability moderated by credit risk. To achieve the research objectives, the research design used is correlational quantitative using secondary data obtained frompublication reportbank. The population of this study were all BPDs throughout Indonesia, amounting to 31 banks. The sampling technique in this study used purposive sampling with a total sample of 25 companies. The data analysis technique used is moderated regression analysis. The results showed that (1) the minimum capital requirement has a positive effect on profitability, (2) credit distribution has a positive effect on profitability, (3) operational efficiency has a negative effect on profitability, (4) credit risk weakens the effect of the minimum capital requirement on profitability, (5) credit risk weakens the effect of lending on profitability, and (6) credit risk strengthens the effect of operational efficiency on profitability. Keywords: minimum capital requirement, lending, operational efficiency, credit risk, profitability